(untitled) (Libellarium: journal for research in the field of information and related sciences, 2015)
Since the very end of the 20th century one can notice the rapid change of the reading paradigm. What meaning can one find in the question “do you read?” This change was influenced by development of ICT, information flood in the electronic space, growing popularity of WWW and possibility to receive information in different ways at the same time. The first mentioned factor affected even the physiology of reading, and children today read in slightly different way in comparison to adults who were introduced to computers in their adulthood. Availability of texts published on the internet raises a question, what kind of relation is between process of reading on the internet and browsing the internet. Could we say that reading a vook is the same thing as reading a book? The third factor – offering information in a few different ways – changes the speed of reading and perception of information. How all those factors can affect not only publishing and reading of books, but also the change of reading paradigm in the nearest future? This paper discusses some of these questions.